New insights into how chromatin remodellers direct CENP-A to centromeres - Prasad, Punit (Nature Publishing Group, 2011)
This article highlights the novel role of SWI/SNF complex in organizing centromeric chromatin and removal of centromeric histone variants from ectopic chromosomal locations as reported by the Owen–Hughes lab.